(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
This article begins by presenting a path of investigation about the grotesque, emphasizing the relationship between the actress and her buffoonish character Ternurinha. The perspective adopted to approach the theme of the grotesque is elaborated from the dialogue with the American linguist Mary Russo, with the professors and researchers in the area of communication at UFRJ Muniz Sodré and Raquel Paiva, and with the Swiss psychoanalyst Carl Jung. Based on this dialogue, it is asked whether the grotesque is necessarily laughable, and about it, the question of researcher, teacher and clown Ana Fuchs is discussed: “What are we laughing at?”. The last part of the article is dedicated to Cabeção, a character created by the dancer, researcher, and player Maria Eugênia Tita, brought to exemplify and help to reflect on the grotesque states that can be perceived from him.